Токсичность наночастиц цинка и его биологические свойства - Глущенко, Н.Н.; Скальный, А.В. (Актуальні проблеми транспортної медицини, 2010)
Развитие современных нанотехнологий позволяет получать наночастицы металлов с заданными физико химическими и биологическими свойствами. При разработке и создании новых лекарственных препаратов на основе наночастиц металлов вопрос токсичности и определение зон их биологического действия при введении в организм является важной и актуальной задачей. В связи с этим, были исследованы токсикологические характеристики наночастиц цинка: МПД, ЛД50, ЛД100 при введении в организм, проведены исследования по выявлению зон биологического действия цинка, разработаны подходы в использовании протективных свойств наночастиц цинка для защиты от алкогольной интоксикации. At present the nanotechnology allows to obtain metal nanoparticles with given physicochemical and biological properties. However during the development of new drugs with metal nanoparticles the assessment of nanoparticles toxicity becomes task of primary importance. We studied the toxicity of zinc nanoparticles: MPD (maximum permissible dose), LD50, LD100. We have shown that in the range of doses 0.05 100 mg/kg zinc nanoparticles exert biotic action i.e. accelerate metabolic processes, in the range of doses 100 450 mg/kg there’s a safety zone, doses more than 450 mg/kg are toxic ones. LD50 of zinc sulfate is 28 times lower comparing with LD50 of zinc nanoparticles. We have also shown that the introduction of zinc nanoparticles reduces voluntary alcohol use and reduces by 40 % the animal mortality after alcohol intoxication. The mechanism of protecting action of zinc nanoparticles will be discussed.